International perspectives - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Oxford : Elsevier JAI, 2007)
Research in learning and behavioral disabilities, employing a variety of methods and techniques, has provided a wealth of information relevant to practitioners. In order to be of value, however, this research must employ appropriate and rigorous methodology. Recent years have witnessed a variety of new techniques for research synthesis, research design, and data analysis, many of which have been applied to the study of learning and behavioral disabilities. In this volume, a variety of methodological approaches to research is described, applied, and evaluated. Chapters in this volume provide discussions of applications of qualitative research methodology, and techniques for statistical analysis for single subject data. In addition, techniques for structural equation modeling and item response theory are described with specific reference to the study of learning and behavioral disorders, as are techniques for handling missing data. Also discussed are procedures for dealing with specific research problems in areas such as behavioral disorders, school-wide intervention systems, and early reading as well as more general literacy interventions. Finally, methodology for integrative research reviews are described, as well as applications of research synthesis to quantitative research on cognitive processes in mathematics, and to qualitative research in co-teaching. This volume contains chapters authored by internationally recognized experts in the field of learning and behavioral disabilities. This book is intended for interested professionals and practitioners; researchers in learning and behavioral disabilities; and graduate students in psychology, education, and special education, particularly those interested in applications of research methodology in the study of learning and behavioral disabilities. It discusses, applies and evaluates different methodological approaches to learning and behavioral disorder research; has internationally recognized contributors; and serves as a practical reference to educators, researchers, psychologists, professionals and practitioners.
Working memory and early mathematics: possibilities for early identification of mathematics learning disabilities / Evelyn H. Kroesbergen, Bernadette A.M. Van de Rijt, Johannes E.H. Van Luit -- Reading development and reading disabilities: focus on Norway / Solveig-Alma H. Lyster -- Ecological perspectives on student behaviour: why teachers in training need to see the bigger picture / Julian G. Elliott -- Reading comprehension instruction for students with learning disabilities / Sheri Berkeley -- Goal orientations and classroom goal structures as predictors of classroom behaviors for Greek students with and without learning difficulties: clarifying the differential role of motivational orientations / Georgios D. Sideridis -- Parenting stress in families of children with Attention-Deficit/Hyperactivity Disorder: the impact of ADHD subtype and Oppositional Defiant Disorder comorbidity / Ana Miranda, Rafaela Marco, Dolores Grau -- The problem of measuring socio-cultural level in psychological research / Alessandra Coscarelli, Giulia Balboni, Roberto Cubell -- Students with mathematical disabilities in Belgium: from definition, classification and assessment to STICORDI devices / Annemie Desoete -- ADHD at five: a diagnosis-intervention program / Anna Maria Re, Cesare Cornoldi -- Evaluation of social abilities in educational contexts: a challenge for students with communication difficulties / Mónica Elisabeth Castilla -- Focus on international schools: serving students with learning disabilities / Beverly D. Shaklee -- The development of numerical intelligence in preschool children with cochlear implants: a hypothesis on mathematical, verbal, and non-verbal cognitive competence / Daniela Lucangeli, Elisabetta Genovese, Marco Gubernale, Silvia Cabrele, Daniele Manzoni -- Co-teaching in inclusive classrooms: results of qualitative research from the United States, Canada, and Australia / Kimberly A. McDuffie, Thomas E. Scruggs, Margo A. Mastropieri.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Learning disabilities; Learning disabled children -- Education; Attention-deficit hyperactivity disorder; Teaching of students with specific learning difficulties / needs; Education -- Special Education -- Learning Disabilities